2023
DOI: 10.3390/vaccines11081350
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance and Hesitancy among Healthcare Workers in Lusaka, Zambia; Findings and Implications for the Future

Steward Mudenda,
Victor Daka,
Scott K. Matafwali
et al.

Abstract: The uptake of COVID-19 vaccines is critical to address the severe consequences of the disease. Previous studies have suggested that many healthcare workers (HCWs) are hesitant to receive the COVID-19 vaccine, further enhancing hesitancy rates within countries. COVID-19 vaccine acceptance and hesitancy levels are currently unknown among HCWs in Zambia, which is a concern given the burden of infectious diseases in the country. Consequently, this study assessed COVID-19 vaccine acceptance and hesitancy among HCWs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 130 publications
3
3
0
Order By: Relevance
“…This study found an outstanding vaccine uptake among HCWs, with more than three-quarters (85.9%) of participants having received at least one dose of the COVID-19 vaccine. The high COVID-19 vaccination rate among HCWs in Ghana is similar to high rates reported by other researchers, such as a vaccination rate of 72.1% in Zambia [39], 77.0% in China [64], 82.5% in Malawi [65], and 70.5% in Egypt [66]. In contrast to these findings, formative studies conducted before the COVID-19 vaccines were rolled out reviewed that most HCWs had concerns about the vaccines and were not willing to get vaccinated once vaccines were made available.…”
Section: Uptake Of Covid-19 Vaccination Among Hcwssupporting
confidence: 88%
See 1 more Smart Citation
“…This study found an outstanding vaccine uptake among HCWs, with more than three-quarters (85.9%) of participants having received at least one dose of the COVID-19 vaccine. The high COVID-19 vaccination rate among HCWs in Ghana is similar to high rates reported by other researchers, such as a vaccination rate of 72.1% in Zambia [39], 77.0% in China [64], 82.5% in Malawi [65], and 70.5% in Egypt [66]. In contrast to these findings, formative studies conducted before the COVID-19 vaccines were rolled out reviewed that most HCWs had concerns about the vaccines and were not willing to get vaccinated once vaccines were made available.…”
Section: Uptake Of Covid-19 Vaccination Among Hcwssupporting
confidence: 88%
“…Conversely, two other studies found acceptance rates of 70.0% [ 22 ] and 78.6% among HCWs in Ghana, exceeding the regional acceptance rate in Africa [ 38 ]. Key determinants of vaccine hesitancy among HCWs, particularly in developing countries included concerns about vaccine effectiveness [ 39 ], knowledge about the vaccine [ 40 , 41 ], attitude towards vaccination [ 35 , 42 , 43 ], and health belief model measures, including perceived susceptibility to and severity of COVID-19 infection [ 44 , 45 ], perceived barriers and benefits to vaccination [ 42 ], and cues to action [ 46 ]. Globally, perceived COVID-19 vaccine effectiveness among the general population ranged from 67.8% to 95.9%, and factors such as age, sex, level of education, and marital status significantly influenced individual perception of vaccine efficacy [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study found an outstanding vaccine uptake among HCWs, with more than three-quarters (85.9%) of participants having received at least one dose of the COVID-19 vaccine. The high COVID-19 vaccination rate among HCWs in Ghana is similar to high rates reported by other researchers, such as a vaccination rate of 72.1% in Zambia [55], 77.0% in China [56], 82.5% in Malawi [57], and 70.5% in Egypt [58]. In contrast to these findings, formative studies conducted before the COVID-19 vaccines were rolled out reviewed that most HCWs had concerns about the vaccines and were not willing to get vaccinated once vaccines were made available.…”
Section: Uptake Of Covid-19 Vaccination Among Hcwssupporting
confidence: 88%
“…This shows that the COVID-19 vaccine acceptance among Indonesian healthcare workers is lower compared to similar studies conducted in Singapore (94.9%) [ 27 ], the United Kingdom (93.4%) [ 28 ], and Lebanon (86.8%) [ 29 ]. On the contrary, healthcare workers in Indonesia were more willing to accept the COVID-19 vaccine compared to the healthcare workers surveyed in the United States (36%) [ 30 ], a joint study conducted in France, Belgium, and Canada (72.4%) [ 31 ], a review of 35 studies conducted globally in 2020–2021 (average vaccine acceptance rate of 77.49%) [ 32 ], in Oman (42.3%) [ 22 ], Zambia (72.1%) [ 33 ], the Democratic Republic of the Congo (DRC) (67.2%) [ 34 ], and Somalia (61%) [ 35 ]. The varying rates of COVID-19 vaccine acceptance illustrate that the vaccine acceptance rate is highly contextual in terms of place and time, varying from one nation to the next and from one time point to the next, is influenced by numerous factors, and is a true reflection of trust and confidence in vaccines, the system delivering them, sources of information on these topics, and in the government and scientific communities.…”
Section: Discussionmentioning
confidence: 99%